Retinal effects of Sildenafil in diabetic patients - Bahir, Abdul-Razzak (Journal of the Faculty of Medicine Baghdad, 2008)
BackgroundSildenafil has been used in the treatment of erectile dysfunction (ED). However it has the disadvantage of many visual disturbances. The aim of this work is to study the effectof sildenafil on diabetic patients which might have ocular problems due to diabetes mellitus.Materials and Methods:A total of 30 subjects were enrolled in the study, they were divided into two groups. The control group consisted of 10 healthy subjects but complaining of ED only and theother (20 patients) had diabetes mellitus and ED as well. All subjects had ocular tests done before and after sildenafil intake. It was obvious that sildenafil changed visual tests from totally normal for controls, before treatent, to visual abnormality in some of the tests after treatment, such as in colour Fac Med Baghdad sense , diplopia & intra ocular pressure ( IOP ).Results:While certain percentage of diabetic patients had visual disturbances even before sildenafil intake. The abnormalities were in visual acuity, visual field and, in fundusappearance. Post – treatment led to increase the percentage of patients with already existing ocular problems and extend them to include some other new ones like change in coloursense , diplopia and increased ( IOP ).Conclusions:Comparing the patient group with the control , pre – treatment tests revealed that diabetic patients had already pre – existing ocular problems due to diabetes such as in thevisual acuity , visual field which were statistically not significant ( p>0.05). The only significant (p